Analysis of Field-Aligned Currents in the High-Altitude Nightside Auroral Region: Cluster Observation - Youra Shin; Ensang Lee; Jae-Jin Lee (Journal of Astronomy and Space Sciences, 2019)
In this paper we present analysis of current density when the Cluster spacecraft pass the nightside auroral region at about 4-5 RE from the center of Earth. The analysis is made when the inter-spacecraft separation is within 200 km, which allows all four spacecraft to be situated inside the same current sheet. On 22 February 2002, two field-aligned current (FAC) events were observed in both the southern and the northern hemispheres. The FACs were calculated with magnetic field data obtained by the four spacecraft using the Curlometer method. The scales of the FACs along the spacecraft trajectory and the magnitudes were hundreds of kilometers and tens of nA/m2, respectively, and both events were mapped to the auroral region in the ionosphere. We also examined reliability of the results with some parameters, and found that our results are adequately comparable with other studies. Nevertheless, some limitations that decrease the accuracy of current estimation exist.